2013
DOI: 10.5603/fhc.2013.0019
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Bcl-2, Bax and Caspase-3 expression in the dermal microvascular endothelial cells and the epidermal layers of the eschar (tache noire) in patients with Mediterranean spotted fever

Abstract: Abstract:Mediterranean spotted fever (MSF) is widely prevalent in many endemic regions in Bulgaria. The disease is still not quite thoroughly studied as to some aspects of its pathogenesis and especially to issues that concern the crucial signals for apoptosis in the target microvascular endothelial cells. To study the expression of Bcl-2 family proteins and Caspase-3 in the dermal capillary endothelial cells from skin papules and in the eschar (tache noire) epidermal layers of patients with MSF so that we can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Amadeus Gladbach et al further discussed that ERK inhibition functioned as a significant role in ischemic stroke [35]. Inhibition of EGR1 may become a potential treatment to improve the outcomes of ischemic stroke because over-expressed EGR1 expression may aggravate brain injury [36]. In addition, the overexpression of Bax could promote the apoptosis of the dermal microvascular endothelial cells in patients with mediterranean spotted fever [37].…”
Section: Discussionmentioning
confidence: 99%
“…Amadeus Gladbach et al further discussed that ERK inhibition functioned as a significant role in ischemic stroke [35]. Inhibition of EGR1 may become a potential treatment to improve the outcomes of ischemic stroke because over-expressed EGR1 expression may aggravate brain injury [36]. In addition, the overexpression of Bax could promote the apoptosis of the dermal microvascular endothelial cells in patients with mediterranean spotted fever [37].…”
Section: Discussionmentioning
confidence: 99%
“…Caspase 3 and BAX are two signals participating in the process of apoptosis [ 35 , 36 ]. Our study showed that ivabradine was associated with the significant dephosphorylation of caspase 3 and BAX, indicating the anti-apoptotic effect of ivabradine in diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNAs generated from the skin biopsies of patients before and after treatment were used to perform the expression analysis of a group of 29 genes involved in key pathways implicated in the pigmentation and homeostasis of the skin cells 8 - 10 , 25 - 42 using the Illumina MiSeq ® Reagent Kit v3 (150 cycle) and the TruSeq Targeted RNA Custom Panel Kit ( Chart 1 ).…”
Section: Methodsmentioning
confidence: 99%